A large‐scale double‐stage‐screw 3D printer for fused deposition of plastic pellets. Issue 31 (3rd April 2017) - Liu, Xiaojun; Chi, Baihong; Jiao, Zhiwei; Tan, Jing; Liu, Fengfeng; Yang, Weimin
ABSTRACT: Fused deposition molding (FDM) is the most popular technology in the fields of three‐dimensional printing, but it is hard to use a variety of plastic materials due to the limitation of filament form of material. Using plastic pellets as printing materials gives advantages in cost, processing speed, and available materials. In this work, a large‐scale double‐screw FDM three‐dimensional printer based on plastic pellets has been designed. It is capable of printing large plastic products at a low cost and high speed. Using ABS + 10%GF as printing material, this work is first focused on the effects of the pressure and speed of the metering screw on the flowrate of melt. The equation for the relationship of these three parameters was established as well. Based on this equation, the effects of melt flow, printing speed, and layer thickness on the width of fused filament were investigated with experiments. Furthermore, the effects of printing spacing between fused filaments on surface accuracy and bonding strength were also explored. By printing models, it was revealed that the designed printer is able to print products with plastic pellets. © 2017 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2017, 134, 45147. Abstract :